Waiting town : Life in transit and Mumbai$1 (Bs other world-class historiess - Bjorkman, Lisa (Delhi: Primus Books, 2024)
Drawing on a decade of ethnographic research in the Indian city of Mumbai, Waiting Town is an unconventional little book - experimental in form - about how we come to know the worlds about which we write. The narrative follows the author's fieldnotes diaries as they wend their way through a series of ethnographic puzzles that emerge in the wake of a high-profile mega-infrastructure project that became an internationally celebrated prototype and model. Waiting Town complicates this celebratory narrative by revealing the conflicting temporalities and procedural pretentions of 'world class' developmentalism. On one level, Waiting Town is a book about Mumbai - about housing schemes and scams, about 'duplicate' documents (and 'duplicate duplicates'), and about the material wreckage wrought by the city's 'world-class' ambitions. And at the same time, it has a larger story to tell about truth and falsehood, time and memory - and about the promises and pitfalls of knowledge production, interpretation and representation more generally.
Keywords: Domestic -- India -- Mumbai; Dwellings -- India -- Mumbai; Political Science / World / Asian